A Cross-sectional Study to Assess the Environmental and Behavioral Risk Factors Associated with Falls in Older Adults Residing in Community Settings of North-east Delhi, India - Monika Kankarwal; Kamli Prakash; Sachin Kumar; Arshad Ayub; Shivam Pandey; Sanchita Pugazhendi (Journal of the Indian Academy of Geriatrics)
Introduction: Environmental and behavioral risk factors play a major role in causing falls among older adults. Consequently, it is critical to comprehend how behavioral and environmental risk factors contribute to falls among older adults living in Indian communities. Aim and Objective: This study aims to explore environmental and behavioral risk factors associated with falls in older adults. To find an association between sociodemographic characteristics and environmental and behavioral risk factors associated with falls in older adults. Materials and Methods: Through a computer-generated random selection, two sublocalities were selected. Based on sample size calculations, a house-to-house survey was carried out among 246 older adults residing in a selected community setting after considering inclusion and exclusion criteria. Data were collected using a sociodemographic survey tool, a home falls and accident screening tool, and a structured modified fall behavior assessment tool. Chi-square, Fischer’s exact test, independent “t”, analysis of variance, and logistic regression were used for statistical analysis. Results: Majority (58.9%) of the older adults were from the age group of 60–65 years, and majority (52.4%) of the subjects were female. The incidence of fall rate among older adults was 35.37%. The majority (66.6%) of older adults had a history of recurrent falls. Among sociodemographic characteristics, females reported 2.2 times more fall rate than male older adults at P ≤ 0.03, respectively. Educated older adults reported 0.3 times less history of falls at statistically significant P = 0.001. Among behavioral risk factors, older adults with no history of falls exhibited 2.3 times higher risky behavior than older adults with a history of falls. Among environmental risks, older adults with a history of falls had 1.5 times higher environmental risk factors. Conclusion: Comprehending and exploring environmental and behavioral risk factors related to falls in older adults will help healthcare professionals develop a need-based fall prevention intervention that will be appropriate and culturally acceptable at the primary prevention level.